Palladium in Heterocyclic Chemistry A Guide for the Synthetic Chemist - Li, Jie Jack.; Gribble, Gordon W. (Burlington : Elsevier Science, 2006)
Palladium chemistry, despite its immaturity, has rapidly become an indispensable tool for synthetic organic chemists. Heterocycles are of paramount importance in the pharmaceutical industry and palladium chemistry is one of the most novel and efficient ways of making heterocycles. Today, palladium-catalyzed coupling is the method of choice for the synthesis of a wide range of biaryls and heterobiaryls. The number of applications of palladium chemistry to the syntheses of heterocycles has grown exponentially. These developments highlight the need for a monograph dedicated solely to the p
Cover; I045116-FM; I045116-01; I045116-02; I045116-03; I045116-04; I045116-05; I045116-06; I045116-07; I045116-08; I045116-09; I045116-10; I045116-11; I045116-12; I045116-13; I045116-14; I045116-Idx
Description based upon print version of record.
Keywords: Heterocyclic compounds -- Synthesis; Heterocyclic compounds; Organopalladium compounds